Artificial Intelligence in Public Sector Governance: A Bibliometric Analysis of Global Research Trends - Muhammad Syahbar; Helen Dian Fridayani; Van Hoa Vu (Institut Pemerintahan Dalam Negeri, 2026)
Abstract Artificial intelligence (AI) has moved from a technical innovation agenda to a governance issue that affects public decision-making, service delivery, organizational capacity, accountability, and citizen rights. Yet the literature is fragmented across information systems, public administration, computer science, law, and policy studies. This study maps the intellectual structure and thematic evolution of global research on AI in public sector governance through a bibliometric analysis of 263 English-language journal articles indexed in Scopus between 2021 and 2025. Bibliometrix/Biblioshiny and VOSviewer were used to examine publication dynamics, keyword frequency, co-occurrence, thematic positioning, and conceptual relationships. The results indicate a rapidly expanding and increasingly differentiated field. AI is the dominant conceptual anchor, while public sector, public policy, public administration, ethical technology, governance, and decision making form the principal connecting themes. The thematic map indicates that digital transformation, decision making, and public sector operate as motor themes; public policy and ethical technology represent an advanced governance-oriented stream; and algorithmic accountability, automation, and decision-support systems remain emerging or weakly integrated. The article argues that the field is shifting from an adoption-centred literature toward an institutional governance literature. It identifies four analytical tensions that require future research: capability versus control, efficiency versus equity, automation versus discretion, and innovation versus democratic legitimacy. The study contributes a research agenda that positions AI as a socio-technical and institutional transformation rather than a stand-alone computational tool. Keywords: Artificial Intelligence; AI Governance; Public Sector Governance; Public Administration; Digital Transformation; Algorithmic Accountability; Bibliometric Analysis Abstrak Kecerdasan buatan (Artificial Intelligence/AI) telah bergeser dari agenda inovasi teknis menjadi isu tata kelola yang memengaruhi pengambilan keputusan publik, penyelenggaraan layanan, kapasitas organisasi, akuntabilitas, dan hak warga negara. Namun, literatur yang berkembang masih tersebar pada bidang sistem informasi, administrasi publik, ilmu komputer, hukum, dan studi kebijakan. Penelitian ini memetakan struktur intelektual dan evolusi tematik riset global mengenai AI dalam tata kelola sektor publik melalui analisis bibliometrik terhadap 263 artikel jurnal berbahasa Inggris yang terindeks Scopus pada periode 2021-2025. Bibliometrix/Biblioshiny dan VOSviewer digunakan untuk menganalisis dinamika publikasi, frekuensi kata kunci, ko-occurence, posisi tematik, dan hubungan konseptual. Hasil penelitian menunjukkan bidang yang berkembang cepat dan semakin terdiferensiasi. AI menjadi jangkar konseptual utama, sedangkan sektor publik, kebijakan publik, administrasi publik, teknologi etis, tata kelola, dan pengambilan keputusan menjadi tema penghubung utama. Peta tematik menunjukkan digital transformation, decision making, dan public sector sebagai motor themes; public policy dan ethical technology sebagai arus tata kelola yang semakin maju; sementara algorithmic accountability, automation, dan decision-support systems masih merupakan tema yang berkembang atau belum terintegrasi kuat. Artikel ini berpendapat bahwa bidang ini bergerak dari literatur yang berpusat pada adopsi menuju literatur tata kelola institusional. Empat ketegangan analitis diidentifikasi untuk agenda penelitian mendatang: kapasitas versus kontrol, efisiensi versus keadilan, otomatisasi versus diskresi, serta inovasi versus legitimasi demokratis. Kata kunci: Kecerdasan Buatan; Tata Kelola AI; Tata Kelola Sektor Publik; Administrasi Publik; Transformasi Digital; Akuntabilitas Algoritmik; Analisis Bibliometrik